Pengaruh Sosialisasi Perpajakan, Kesadaran Wajib Pajak, Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Haninun, Haninun; Lourent, Angelica (CV. Lafadz Jaya, 2022)
Taxation means that people's contributions to the state treasury are personally influenced by the law to give up part of their own wealth. The survey explains that tax socialization is positively affected by mandatory compliance with motor vehicle taxation, awareness of taxpayers and tax penalties is affected by taxpayer compliance when paying taxes on motorized vehicles. The survey uses a quantitative approach that focuses on breadth and objectivity. As a result, the survey can be used to reveal the reality when an area is out of sync. The population in the survey is all mandatory motor vehicle taxation. The sample in the survey is taxpayers who have one or more motorized vehicles and are in the Bandar Lampung area. In Lampung Province alone, the total number of motorized vehicles is 3,679,741 units. This indicates that 6.13% of taxpayers who own two-wheeled vehicles must participate in the whitening and 31.32% of taxpayers who own four-wheeled vehicles must participate in the whitening. This indicates that if the taxpayer is still not aware of the need to pay motor vehicle taxation. The conclusion of the survey is that the introduction of taxation is not affected by mandatory tax compliance, awareness of taxpayers is affected by mandatory tax compliance, tax penalties are not affected by taxpayer compliance.